(Nano)Materiais à base de carbono e nitrogênio obtidos a partir da carbonização hidrotérmica de biomassa - Castro, Antônio Joel Ramiro de (2013)
Currently, biomass has been used as renewable source for energy generation through the combustion process and also for producing biochars and biofuels. In this study, it has been reported an alternative use of biomass to produce new carbonaceous materials aiming to understand their properties to search new applications. The obtained nanomaterials were produced through sustainability approaches. This way, hydrothermal carbonization method (HTC) was used to prepare the nanomaterials, in which chitosan was applied as precursor. Distinct preparations of the nanomaterials (hydrothermal carbon) by varying the carbonization time and temperature were achieved. The nanomaterials were characterized to evaluate their structural, morphological, compositional and textural features. Typical low structural ordering of amorphous carbon was observed for the hydrothermal carbons. Compositional results have shown that the carbon contents increased with increasing both time and temperature of carbonization, reaching carbon amounts up to 55 %. Nitrogen contents varied from 5 to 6 %, independently of the reaction parameters, on the other hand. Additionally, hydroxyl, amines and amides functional groups remained or were produced on solid surfaces. Irregular plate-like morphologies possessing aggregated nanoparticles in micrometer range were observed over the hydrothermal carbons. Indeed, they had surface areas values in the 60-290 m2/g range, depending on the synthesis parameter established. Besides, both chitosan and hydrothermal carbons were pyrolysed in order to compare their aforesaid features. Pyrolysis of the hydrothermal carbons resulted in a defective graphitic-type structure formation. For hydrothermal carbon pyrolysis, the carbon amounts increased with the temperature increments, in accordance with the FTIR results, suggesting a loss of the abovementioned functional groups. After treating the solid with different temperatures, about 7 % of nitrogen was included into the solid structure and it results in a nitrogen-doped carbonaceous material. Hydrothermal carbon pyrolysed at 600 ◦C displayed a product with surface area around 420 m2/g, being seven times higher than that of the precursor counterparts. Although the morphology of the particles was not strongly affected, surface macropores were observed. By increasing the temperature of the pyrolysis process, the direct pyrolysed chitosan exhibited also a graphitic-type structure formation and this structure is originated from a low ordering intermediate. Due to the materials volatilization loss during the chitosan pyrolysis, the conversion of carbon was lesser than 100 %. When pyrolysis was achieved at 300 ◦C, surface area of the solids was 82 m2/g and the textural parameters dropped to values close to zero, indicating a non-porous solid up to 300 ◦C. The features of the nanomaterials produced in this work enable them to act as catalysts supports, new adsorbents and showing promise in agriculture fields as well.